Efektivitas Pengawasan Kepala Sekolah Terhadap Kedisiplinan Guru Madrasah - Ani Apiyani (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to examine the effectiveness of the principal's supervision of teacher discipline in madrasas. Teacher discipline is an important factor in improving the quality of education, and principal supervision has a key role in ensuring standards of discipline. The research method used is descriptive, bibliographic in nature by collecting data in the form of literature. The research results show that effective supervision by school principals contributes significantly to increasing teacher discipline. In addition, it was found that the frequency and quality of supervision, as well as the approach used by school principals, greatly influenced the level of teacher compliance with applicable regulations and procedures. These findings emphasize the importance of the active role of school principals in carrying out structured and consistent supervision to create a disciplined and high-quality educational environment.